Introduction - Sto. Domingo, Mariano R. (Philippine Social Sciences Review; People-in-Environment; Environment-in-People, Ed. Mariano R. Sto. Domingo, 2011)
People-in-Environment, Environment-in-People
Keywords: environment, erosion, biological diversity